Sanguinarine suppresses migration and metastasis in colorectal carcinoma associated with the inversion of EMT through the Wnt/β‐catenin signaling - Zhu, Man (Clin Transl Med, 2020)
BACKGROUND: Unresectable lung or liver organ metastases of colorectal carcinoma (CRC) remain a major obstacle in clinical therapeutics. Epithelial to mesenchymal transition (EMT), a major cause of highly frequent metastasis in tumor, can be promoted by the Wnt/β‐catenin pathway that is aberrantly activated in approximately 90% of CRC. This research aimed to elucidate the antimetastatic potential of sanguinarine (SG) in CRC and the underlying molecular mechanism. METHODS: The in vitro anticancer effect of SG was determined via cell viability experiment and colony formation assay. Xenograft model of nude mice was used to confirm the antitumor effect of SG in vivo. The antimetastatic potential of SG was investigated by the metastasis model of nude mice, hematoxylin and eosin (H&E) staining, migration assay, and wound‐healing analysis. Immunoblotting analysis, immunofluorescence staining, and immunohistochemistry assay were conducted to elucidate the molecular mechanism. RESULTS: In this study, we reported that SG has a selective inhibitory effect on LoVo cells with metastatic characteristics. Furthermore, our results showed attenuation in the migration and metastatic ability of SG‐treated LoVo cells and also decreased metastatic nodules of liver and lung in mice metastasis model. This was also confirmed at the molecular level via H&E staining. Further study revealed that SG had negative impacts on the Wnt/β‐catenin pathway and EMT markers in LoVo cells both in vitro and in vivo. CONCLUSIONS: Taken together, the antimetastatic potential of SG attributed to the suppression of the Wnt/β‐catenin signaling, which further prevented EMT progression. SG may be of value in a potential therapy for the management of metastasis CRC.